Correlation between triglyceride level and carotid intima media thickness in patients with type 2 diabetes mellitus - Bendwal, Kavita; Bendwal, Suresh; Dhawale, R. G. (International Journal of Clinical Trials, 2018)
Background: Type 2 diabetes mellitus (T2DM) is associated with the development of premature atherosclerosis and high cardiovascular morbidity and mortality. Diabetic dyslipidemia is believed to play an important role in the pathogenesis of accelerated atherosclerosis in this condition. The aim of present study was to find out the role of fasting and postprandial triglyceride level and its relation with carotid intima media thickness in patients of T2DM. Methods: 120 patients of T2DM were included in this study. All patients didn’t have any peripheral vascular disease, IHD or stroke and all were between 30 to 70 years of age. Ultrasonographic evaluation done in all patients to measure CIMT and its correlation seen with fasting and postprandial triglyceride level and other parameters. Results: All patients are divided into 3 groups according to their triglyceride level NN, NH and HH. The mean CIMT in the NN, NH and HH group was 0.96±0.26, 1.64±0.39 and 1.94±0.57 mm respectively. The CIMT was higher in the NH and HH groups in comparison with that in NN group which is statistically significant (p<0.001). Conclusions: Fasting and postprandial triglyceride level both correlate significantly with carotid intima media thickness. But the correlation of postprandial triglyceride level with CIMT is better than that of fasting triglyceride level.